722 SAFE (SUPERCHARGED CERVICAL ANASTOMOSIS FOR ESOPHAGECTOMY AND GASTRIC PULL-UP) PROCEDURE: LONG TERM RESULTS FROM 61 PATIENTS. (17th September 2021) - Takeda, F; Tutihashi, R; Aissar Sallum, R; Busnardo, F; Ribeiro, U; Cecconello, I; Nahas, S
Abstract: : Esophagectomy still represents a challenge surgical procedure. Anastomotic leakage is the most feared complication and is likely related to diminished anastomotic perfusion. 'Supercharged' microvascular anastomosis has been performed in select patients to supplement the blood supply to the graft and anastomosis, after esophagectomy. This study aimed to evaluate results after performing the supercharged cervical anastomosis for esophagectomy procedure. Methods: This prospective cohort study evaluated patients who underwent esophagectomy with gastric reconstruction and cervical anastomosis for locally advanced esophageal carcinoma. Patients were selected in which cervical anastomosis using the supercharged cervical anastomosis for esophagectomy procedure was performed. The anastomotic perfusion areas were evaluated using indocyanine and SPY before and after supercharged cervical anastomosis for esophagectomy. Post esophagectomy complications were also recorded. Results: The study enrolled 61 patients, which included 47 (77.0%) men, with a mean age of 67.3 years. Median additional surgical time was 112 min (IQ 90–180), Leakage occurred in 1.6% of the patients (microanastomosis thrombosis), whereas the corresponding anastomotic stricture rates were 3.2% (mean follow-up was 25 mounths). Perfusion analyses showed a 28% improvement in the anastomotic area after venous anastomosis and a 37% improvement after arterial and venous anastomosis. Conclusion: The supercharged cervical anastomosis for esophagectomy procedure may be related to low occurrence of anastomotic leakage and improve perfusion in the anastomotic area via vein and arterial microanastomoses.